Optimalisasi Pengetahuan Ibu Tentang Pemanfaatan Ikan Lele Sebagai Nutrisi Tinggi Protein Guna Menekan Kejadian Stunting Pada Balita Di Wilayah Kerja Polindes Senggreng Kabupaten Malang - Rohmah, Miftakhur; Nuryati, Ida; Putri, Ella Wiyasa; Fauziyah, Eni; Winarti, Lilik; Anggraeni, Ria; Ravita D, Nena; Dwinanda R, Elvira; Candrawargani, Devy Tri (Yayasan Inspirasi El Burhani, 2025)
Introduction: In 2017 the government launched the National Action Plan for stunting management at the national level, especially at the village level. One part of the program is the prevention of stunting that occurs in the community. Because most people do not understand stunting correctly, and think that the term stunting or dwarfism commonly used in society is a hereditary factor. Objective: The purpose of this service was carried out to increase knowledge and participation in stunting prevention in toddlers which is expected to directly motivate the community to participate in paying attention to the growth and development of their children by utilizing catfish ( IKAN LELE ) as a source of high protein to prevent and reduce the incidence of. Method: This public service was conducted by 3 phases of activity, namely preparation, implementation and evaluation. Mother's knowledge was measured using a pre-test before the activity and a post-test after being given knowledge. Result: Based on the results of the pretest and posttest which were attended by 15 respondents, it can be stated that the results of the pretest regarding the level of knowledge of respondents regarding the stunting prevention program amounted to 6 respondents (40%) understood the stunting prevention program while based on the results of the post test there were 9 respondents (77.1%) ) who understand stunting prevention programs. Conclusion: Community service activities regarding Stunting Prevention in Pregnant Women and Mothers of Toddlers in Senggreng Village, Sumberpucung received an enthusiastic response from the residents of Senggreng, especially cadres, pregnant women and mothers of toddlers.